EFEKTIVITAS SELF CONTAINED BREATHING APPARATUS (SCBA) DI KONDISI FIRE FIGHTING DRILL DAN KEDARURATAN DI MV PAN BONITA - Muhammad Fasha Naval; Prolin Tarigan Sibero; Bachri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to determine the effectiveness of using a Self Contained Breathing Apparatus (SCBA) in fire fighting drill and emergency conditions on board MV Pan Bonita. SCBA is an air breathing apparatus used by the fire rescue team to help extinguish fires and evacuate casualties on the ship. Based on the researcher's experience during sea practice, the understanding and use of SCBA on board has not been maximized. This study used a qualitative descriptive method with data collected through observation, interviews, documentation, and literature review. The results indicate that SCBA usage has not been fully effective due to several factors including lack of education and supervision from ship officers, lack of crew discipline, and insufficient crew experience. Recommendations include regular monthly training, pre-drill education sessions, strengthened crew discipline and performance, and increased safety awareness and professionalism.